Social Network Analysis of Fan Activism in #BintangEmonBestBoy - Anugrah Bangun, Cendera Rizky; Ariestya, Angga (Universitas Semarang, 2024)
Introduction: Fandom movement in socio-political issues has received attention recently. In Indonesia, this fan movement can be seen when Bintang Emon was reported to be involved in drugs, K-Popers immediately worked hand in hand to help by raising the hashtag #BintangEmonBestBoy to become trending topic on Twitter. Fans can mobilize many people through small groups on each fan base. Methods: This research employs social network analysis to get an overview of the structure and pattern of relationships between actors in a network of K-Pop fandom accounts. By mapping out relationships between individual users, the study identifies key nodes and the flow of information within the community. Findings: Response from K-pop fans in the hashtag #BintangEmonBestBoy can be interpreted as a fan activism. There is no tight connection or cohesiveness between fan activism and political participation realistically, rather it is only sporadic activism in the online realm that is inclined to be clicktivism. Originality: The novelty of this research lies in the mobilization of K-pop fandoms, specifically on how these fan groups participate in online movements and influence social issues, with or without communities. By applying SNA to K-pop fandoms, one can better understand the underlying structure of fan participation and identify key actors who drive fan-based social movements within the network. The chamber-echo effect from the hashtag shows how digital communities leverage their collective power for advocacy, suggest a new type of democracy built on social media disrupting conventional type of popular culture and activism.